Obtención de un hidrolizado de proteína de Aequindens rivulatus (Vieja Azul), utilizando enzimas proteolíticas, Machala , 2014. - Ortega Sánchez, Giovanny Patricio (2015)
In this investigation a protein hydrolyzate of aequidens rivulatus (blue old) using proteolytic enzymes (GRANOZYME ACC), in which an experimental design of six treatments with 12 replicates was applied was obtained where treatments A (1ml), C ( 2ml) and E (3 ml) conducted at a temperature of 28 o C for 24 hours, they were not hydrolyzed, and the enzyme catalyzed not the substrate at this temperature. While the remaining treatments B (1 ml), D (2 mL) and F (3ml) conducted at a temperature of 55 ° C for 24 hours when hydrolyzed reaching treatment D higher significant concentration with 90.3% followed by F with 88.9% and 85.5% only I reach treatment B with a kinematic viscosity of 0.15 mm2 / s. also it obtained a 24% protein, 73% humidity, with 2% fat and 1% ash as physical and chemical analyzes. According to this characterization of the raw material protein percentage of fish old blue it reached 20%, with 76% moisture, 3% fat and 2% ash this was made to facilitate the hydrolyzate by applying protease enzymes comparison of the raw material and the protein hydrolyzate obtained.